# How do you prove #Csc(x) - Cos(x)Cot(x) = Sin(x)#?

see below

By signing up, you agree to our Terms of Service and Privacy Policy

To prove that csc(x) - cos(x)cot(x) = sin(x), we can start with the left-hand side of the equation and use trigonometric identities to simplify it step by step.

Starting with:

csc(x) - cos(x)cot(x)

We know that csc(x) = 1/sin(x) and cot(x) = cos(x)/sin(x). Substituting these into the expression, we get:

1/sin(x) - cos(x)(cos(x)/sin(x))

Next, we simplify:

= 1/sin(x) - cos^2(x)/sin(x)

Now, we find a common denominator:

= (1 - cos^2(x))/sin(x)

We recognize that 1 - cos^2(x) = sin^2(x) (using the Pythagorean identity). Substituting this into the expression, we get:

= sin^2(x)/sin(x)

= sin(x)

Therefore, csc(x) - cos(x)cot(x) simplifies to sin(x), which completes the proof.

By signing up, you agree to our Terms of Service and Privacy Policy

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7